Pengaruh Kepemilikan Institusional, Manajemen Laba, Profitabilitas, dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan Property Dan Real Estate Periode 2020-2022 - Aldy Nova Ramadhoni; Unggul Purwohedi; Ayatulloh Michael Musyaffi (Jurnal Mutiara Ilmu Akuntansi, 2023)
This research aims to examine the influence of institutional ownership, earnings management, profitability, and leverage on firm value. The population in this study consists of companies in the property and real estate sector. The sample size for this study includes 29 companies with a total of 81 observations. The sampling technique employed is purposive sampling. The research method used is quantitative, with secondary data as the data source. The data analysis method involves multiple linear regression analysis using SPSS version 26. The results of this study empirically demonstrate that profitability has a positive and significant impact on firm value. On the other hand, institutional ownership, earnings management, and leverage do not have a significant influence on firm value.